Ultra-high-power repetitive solid state DBD-based switching; The 28th IEEE International Conference on Plasma Science and 13th IEEE International Pulsed Power Conference, Las Vegas, NV, june 17-22, 2001; Vol. 1 - Rukin S. N.; Alichkin E. A.; Lyubutin S. K.; Mesyats G. A. Gennady Andreyevich; Slovikovsky B. G. (2001, 2001)
В фонде НТБ ТПУ отсутствует